PENGARUH PENGALAMAN KERJA, INDEPENDENSI, DAN KOMPETENSI TERHADAP KUALITAS HASIL PEMERIKSAAN DENGAN KEPATUHAN ETIKA AUDITOR SEBAGAI VARIABEL PEMODERASI - Samsi, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
The purpose of this study is to know the influence of: (1) the auditor experience work toward the quality of inspection results; (2) the auditors independence toward the quality of inspection results; (3) the auditor competences toward the quality of inspection results; (4) the interaction between work experience and auditor compliance ethics toward quality of inspection results, (5) the interaction between the independence and compliance auditor ethics toward the quality of inspection results; and (6) the interaction between competence and compliance auditor ethics toward the quality of the inspection results.. This research is a quantitative study, determining sample using purposive sampling / judgment sampling, and to test hypotheses using multiple regression statistical methods (Multiple Regression). Results of analysis shows that the variables; work experience, independence, work experience and interaction of compliance auditor ethics, and the interaction of the independence and compliance auditors ethics have an effect on the quality of inspection result. While the variables; competence and interaction competence and compliance auditor ethics have no effect on the quality of inspection result . Keywords : Work experience, independence, competence, auditor ethics, audit quality.